1997
DOI: 10.1055/s-2007-1023030
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose-Heparin versus niedermolekulares Heparin zur Thromboseprophylaxe in der operativen gynäkologischen Onkologie

Abstract: Zusammenfassung: In eine r prospekt iven dop pelb lind randomisierte n Studie wurden Wirksa m ke it und Vert räg lichke it e ine s niederm oleku lar en Heparins (M on o-Embol ex NM, Sandoz AG, Nürn berg) mi t unfraktio niertem Kalzium Hepari n in der Proph ylaxe post op erative r Venenthro m bosen be i gynäko log ischen Ma ligno mpatienti nne n ver g liche n. 2 h präoperativ und da nn in S-h-Intervallen postoper at iv erhielten 164 Pat ientinn en 3 x 50 000 IE unfraktion iert es Heparin (UFH) und 160 Patienti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, neither TAT, Ddimer nor prothrombin fragment Fl + 2 significantly changed and the authors concluded that CMF therapy did not initiate disseminated intravascular coagulation (DIC). This view is supported by a study in which serial coagulation assays performed before each of six cycles , 4. Studies on changes in blood coagulation and blood rheology during hormonal cytoreductive therapy in breast cancer and miscellaneous cancer patients DVT, deep vein thrombosis; FPA, fibrinopeptid A; MPCA, monocyte procoagulant activity; TPA, tissue plasminogen activator; uPA, urokinasetype plasminogen activator; PAI-1, -2, plasminogen activator inhibitor type I or type 2; aPTT, activated partial thromboplastin time, PT, prothrombin time; TT, thrombin time; AC, adriamycin/cyclophosphamid; MPA, medroxyprogesterone acetate; PIP, plasmin inhibitor plasminogen; FDP, fibrinogen degradation products; CT, chemotherapy; JABCS, Japan Advanced Breast Cancer Study Group; ag, antigen; act, activity.…”
Section: Chemotherapymentioning
confidence: 91%
See 2 more Smart Citations
“…However, neither TAT, Ddimer nor prothrombin fragment Fl + 2 significantly changed and the authors concluded that CMF therapy did not initiate disseminated intravascular coagulation (DIC). This view is supported by a study in which serial coagulation assays performed before each of six cycles , 4. Studies on changes in blood coagulation and blood rheology during hormonal cytoreductive therapy in breast cancer and miscellaneous cancer patients DVT, deep vein thrombosis; FPA, fibrinopeptid A; MPCA, monocyte procoagulant activity; TPA, tissue plasminogen activator; uPA, urokinasetype plasminogen activator; PAI-1, -2, plasminogen activator inhibitor type I or type 2; aPTT, activated partial thromboplastin time, PT, prothrombin time; TT, thrombin time; AC, adriamycin/cyclophosphamid; MPA, medroxyprogesterone acetate; PIP, plasmin inhibitor plasminogen; FDP, fibrinogen degradation products; CT, chemotherapy; JABCS, Japan Advanced Breast Cancer Study Group; ag, antigen; act, activity.…”
Section: Chemotherapymentioning
confidence: 91%
“…4.8% (range of means: 3.1-9.3%) was recorded. This is more than twice as high as compared to the average mean rate of 1.7% (range of means: 0-5.6%) found in eight studies during tamoxifen mono therapy based on a total of 3,184 patients without metastasis (7,54,63,64,(67)(68)(69)(70).…”
Section: Thrombosis Incidencementioning
confidence: 92%
See 1 more Smart Citation
“…However, meta‐analyses on a drug class may fail to document a clinical effect in terms of efficacy/safety ratio when the different drugs behave differently in the various studies. In effect, when compared to UFH, some LMWHs showed better efficacy but equal safety [4,5], others better safety but equal efficacy [6–8], and still others equal efficacy but lower safety [9]. Halving the dose of the latter LMWH proved safer but less effective [10,11]; incidentally, this half‐dosage had been shown to be equally efficacious but safer than UFH [12]· Such conflicting results may annihilate one another when pooled in a meta‐analysis.…”
Section: ‘In Vivo’ A‐xa Activity After Administration Of Different Domentioning
confidence: 99%